Local ablation therapy with contrast-enhanced ultrasonography for hepatocellular carcinoma: a practical review - Kim, Tae Kyoung (Ultrasonography, 2015)
A successful program for local ablation therapy for hepatocellular carcinoma (HCC) requires extensive imaging support for diagnosis and localization of HCC, imaging guidance for the ablation procedures, and post-treatment monitoring. Contrast-enhanced ultrasonography (CEUS) has several advantages over computed tomography/magnetic resonance imaging (CT/MRI), including real-time imaging capability, sensitive detection of arterial-phase hypervascularity and washout, no renal excretion, no ionizing radiation, repeatability, excellent patient compliance, and relatively low cost. CEUS is useful for image guidance for isoechoic lesions. While contrast-enhanced CT/MRI is the standard method for the diagnosis of HCC and post-ablation monitoring, CEUS is useful when CT/MRI findings are indeterminate or CT/MRI is contraindicated. This article provides a practical review of the role of CEUS in imaging algorithms for pre- and post-ablation therapy for HCC.